Diagnosis and management patients with cervical insufficiency - Yu E Dobrokhotova; E I Borovkova; S A Zalesskaya; E A Nagaitseva; D P Raba (IP Berlin A.V., 2018)
The article is devoted to diagnostic methods, therapy possibilities and algorithms of management of patients with cervical insufficiency. Risk factors for the development of isthmic-cervical insufficiency are the acquired and congenital anomalies of the cervix. The diagnosis is only valid during pregnancy. Shortening the length of the cervix